The complete genome sequence of quail coronavirus identified in disease surveillance on quail farms in South Korea - Hye-Ryoung Kim; So-Hyeon Kim; Hoang Duc Le; Jae-Kyeom Kim; Moon Her (Poultry Science)
Avian carcasses collected from 103 flocks on 14 quail farms in Korea between 2022 and 2023 were diagnosed with viral diseases (22 flocks), bacterial disease (58 flocks), parasitic diseases (28 flocks) and non-infectious diseases (60 flocks). The only viral disease identified was viral enteritis in quails that showed pathological lesions in duodenum and appeared to be caused by quail coronavirus (QcoV) through viral metagenomics and RT-PCR assay. Two complete genomes of QCoV from samples diagnosed as viral enteritis were obtained using amplicon-based whole genome sequencing. The two QcoVs were gammacoronavirus, but were distinct from other avian coronaviruses. The spike genes of QCoV have 86.2 ∼ 87.1 % identity with that of American turkey coronavirus, but other gene sequences of QcoV was found to be similar to those of Korean infectious bronchitis virus. Genetic analysis based on the complete genomic sequences found QCoVs had a genetic structure similar to avian coronaviruses, yet it seems to be a unique pathogen specific to quail. This is the first report about the complete genome and genetic analysis of QCoV and the result of disease surveillance in quail in South Korea.